Protective effects of taurine on imidacloprid-induced DNA damage and reproductive performance in the drosophila melanogaster model - Arslan Acaröz, Damla; İnce, Sinan; Zemheri Navruz, Fahriye; Bayşu Sözbilir, Nalan (Afyon Kocatepe Üniversitesi)
Imidacloprid is a neonicotinoid group insecticide and is widely used in veterinary medicine for the control of pests such as lice and fleas in domestic animals. Insecticides are known that they induce toxic effects on living organism, causing oxidative stress and DNA damage. Taurine plays a role in many physiological and biochemical functions and provides an antioxidant effect by stabilization of biological membranes. This study investigated the effect of imidacloprid on DNA damage and reproductive performance and the possible protective effect of taurine in Drosophila melanogasters. Imidacloprid (0.6 µM) alone or in combination with taurine (1, 2 ve 3 mM) were given to broths for 20 days. The results of the study showed that imidacloprid application decreased reproductive performance and increased DNA damage in groups, whereas these effects decreased with taurine administration. In conclusion, it was determined that the adverse effects of imidacloprid regarding DNA and reproductive performance in Drosophila melanogasters were prevented by taurine application.

İmidakloprid, neonikotinoid grubu bir insektisid olup evcil hayvanlarda bit ve pire gibi zararlı böceklerin kontrolü için veteriner hekimlik alanında yaygın olarak kullanılmaktadır. İnsektisitlerin canlılarda toksik etki gösterdiği, oksidatif strese ve DNA hasarına neden olduğu bilinmektedir. Taurin birçok fizyolojik ve biyokimyasal olayda rol almakta ve biyolojik membranlarda stabilizasyonunu sağlayarak antioksidan etki göstermektedir. Bu çalışmada imidaklopridin DNA hasarı ve üreme performansına etkisi ve buna karşın taurinin olası koruyucu etkisi Drosophila melanogaster’lerde araştırıldı. İmidakloprid (0,6 µM) tek başına ve taurin (1, 2 ve 3 mM) ile birlikte besi yerlerine 20 gün boyunca ilave edildi. Çalışmanın sonuçları, imidakloprid uygulamasının gruplarda üreme performansını azalttığını ve DNA hasarında artış meydana getirdiğini, buna karşın taurin uygulaması ile bu etkilerin azaldığını gösterdi. Sonuç olarak Drosophila melanogaster’lerde imidaklopridin DNA ve üreme performansında yol açtığı olumsuz etkilerin taurin uygulaması ile engellendiği belirlendi.
Drosophila melanogaster modelinde imidakloprid ile i̇ndüklenen DNA hasarı ve üreme performansı üzerine taurinin koruyucu etkileri
Keywords: Taurine; Imidacloprid; DNA Damage; Drosophila Melanogaster